Gadget-Based Digital Literacy in Learning Writing Skills for Elementary School Students - Apriyanti, Suciati Nur; Rahman, Rahman (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2021)
Technological developments continue to influence all aspects of life in the world including education. Realizing this, the Ministry of Education and Culture designed the digital literacy movement as a tool to increase the ability to use digital technology in education, especially for teachers and students. Digital literacy can also be used as a tool to improve students' writing skills. However, students are less interested in learning to write. The main difficulty in writing is the inability of students to put their ideas or ideas into writing, this is natural because students rarely practice their writing skills directly. Teachers can apply gadget-based digital literacy in learning writing skills. This study aims to describe gadget-based digital literacy in learning writing skills. Through the literature study method, researchers found that the importance of digital literacy competency learning programs for students has a positive impact on understanding and skills in using digital media. Gadget-based digital literacy results in creative and innovative learning. The use of gadget-based digital literacy can improve students' writing skills.